1997
DOI: 10.1007/s002510050324
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness among Basques, Portuguese, Spaniards, and Algerians studied by HLA allelic frequencies and haplotypes

Abstract: HLA-A, -B, -DRB1, -DQA1, and DQB1 alleles were studied in Iberian and Algerian populations by serology and DNA sequence methodologies. The genetic and cultural relatedness among Basques, Spaniards, and paleo-North Africans (Berbers or Tamazights) was established. Portuguese people have also maintained a certain degree of cultural and ethnic-specific characteristics since ancient times. The results of the present HLA study in Portuguese populations show that they have features in common with Basques and Spaniar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
3
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 14 publications
7
101
3
6
Order By: Relevance
“…Berber characteristics drives the conclusion that the main ancestors that they are main "Guanches" ancestors. However, autosomal HLA characters common to Iberian and Berbers are formed (Arnaiz-Villena et al, 1997) and conjoint autosomal, mtDNA and Y chromosome markers study revealed a gene flow across the Strait of Gibraltar; it was ongoing in high rates since pre-Neolithic times (Currat et al, 2010). This makes difficult a distinction between Iberian and North West Africans on the bases of both autosomal and sex chromosomes markers.…”
Section: Origin Of First Canary Islands Inhabitants According To Hla mentioning
confidence: 99%
“…Berber characteristics drives the conclusion that the main ancestors that they are main "Guanches" ancestors. However, autosomal HLA characters common to Iberian and Berbers are formed (Arnaiz-Villena et al, 1997) and conjoint autosomal, mtDNA and Y chromosome markers study revealed a gene flow across the Strait of Gibraltar; it was ongoing in high rates since pre-Neolithic times (Currat et al, 2010). This makes difficult a distinction between Iberian and North West Africans on the bases of both autosomal and sex chromosomes markers.…”
Section: Origin Of First Canary Islands Inhabitants According To Hla mentioning
confidence: 99%
“…Some authors 28,29 studied HLA variation, and suggested, based on similar frequencies for some haplotypes, that Basques and Berbers had a common origin. This conclusion was challenged by new data and a proper numerical analysis.…”
Section: Strs In North-west African Populations E Bosch Et Almentioning
confidence: 99%
“…In addition to the large and growing literature relating patterns of MHC polymorphism to known or inferred historical migration patterns (Arnaiz-Villena et al 1997;Erlich et al 1997;Grahovac et al 1998;Hatta et al 1999), there has recently been interest in using genes under balancing selection to study population differentiation directly. These studies assume that genes under selection can possibly tell us something about differentiation due to selective differences among subpopulations, which may be of particular interest in some species that are targets of conservation efforts, such as salmon Kim et al 1999) or bighorn sheep (Boyce et al 1997).…”
mentioning
confidence: 99%